Study of Charge Density Distributions and Elastic Charge Form Factors for 40Ca and 48Ca - Ridha, Arkan R (Al-Nahrain Journal of Science, 2017)
The ground charge density distributions (CDD), elastic charge form factors and proton, charge, neutron, and matter root mean square (rms) radii for stable 40Ca and 48Ca have been calculated using single-particle radial wave functions of Woods-Saxon (WS) and harmonic-oscillator (HO) potentials. Different central potential depths are used for each subshell which is adjusted so as to reproduce the experimental single-nucleon binding energies. An excellent agreement between the calculated rms charge radii and experimental data are found for both nuclei using WS and HO potentials. The calculated proton rms radii for 40Ca are found to be in good agreement with experiment data using both WS and HO potentials while the results for 48Ca showed an overestimation in WS potential and slight overestimation in HO potential. The calculated neutron rms radii are found to be well predicted in HO potential for both 40Ca and 48Ca, while there is overestimation in WS results for both isotopes. The calculated rms matter radii showed good agreement with experimental data for 40Ca using WS potential while the result is underestimated in HO potential. For 48Ca, the results obtained with HO potential is underestimated and slightly underestimated with WS potential. For both nuclei, the calculated ground charge density distributions evaluated with WS are in better agreement with the data than those of HO potential. Finally, the results of the calculated elastic charge form factors demonstrate excellent agreement with experimental data for both nuclei under study in WS potential on contrary to the results of HO potential which are completely failed to predict the existence of third diffraction minimum.